Origins of the Bill of Rights - Levy, Leonard W. (Leonard Williams), 1923-2006 (New Haven, Conn. : Yale University Press, 1999)
In this history of the origins of the Bill of Rights, Pulitzer Prize-winning historian Leonard W. Levy offers a panoramic view of the liberties secured by the first ten amendments to the Constitution. Levy illuminates the behind-the-scenes maneuverings, public rhetoric, and political motivations of James Madison and others who overcame fierce opposition to ensure the ratification of these crucial liberties.
Why we have the Bill of Rights -- Habeas corpus -- Bills of attainder -- The First Amendment: the Establishment Clause -- The First Amendment: the Free Press Clause -- The right to bear arms -- The Fourth Amendment: search and seizure -- The Fifth Amendment: the right against self-incrimination -- Double jeopardy -- The double jury system: grand and petty -- The Eight Amendment -- The Ninth Amendment: unenumerated rights.
Includes bibliographical references (pages 297-298) and index.
Print version record.
JSTOR
Keywords: United States. -- History; Constitution (United States); Civil rights -- United States -- History; Droits de l'homme -- États-Unis -- Histoire; LAW -- Constitutional; LAW -- Public; Civil rights; United States; Grondrechten; Bill of Rights (Verenigde Staten); Verenigde Staten; Droits de l'homme -- Etats-Unis -- Histoire; Etats-Unis -- Histoire constitutionnelle; Etats-Unis -- Constitution -- Amendements (01er-10e) -- Histoire; History